Pseudo-dipole signal removal from WMAP data - Liu, Hao; Li, TiPei (Chinese science bulletin, 2011)
We have discovered in our previous work that different observational systematics, e.g. errors from antenna pointing directions or an asynchronism between the attitude and science data may generate a pseudo-dipole signal in the full-sky maps of the cosmic microwave background (CMB) anisotropy that have been published by the Wilkinson Microwave Anisotropy Probe (WMAP) team. We have found that the antenna sidelobe response to the Doppler signal produces a similar effect. In this work, independent from the sources, we have uniformly modeled the pseudo-dipole signal and have removed it from the published WMAP7 CMB maps by model fitting. The result demonstrates that the released WMAP CMB quadrupole is almost completely artificial.